Tang China in Multi-Polar Asia : A History of Diplomacy and War - Wang, Zhenping (Book collections on Project MUSE., 2013)
"Using a synthetic narrative approach, this ambitious work uses the lens of multipolarity to analyze Tang China's (618-907) relations with Turkestan; the Korean states of Koguryŏ, Silla, and Paekche; the state of Parhae in Manchuria; and the Nanzhao and Tibetan kingdoms. Without any one entity able to dominate Asia's geopolitical landscape, the author argues that relations among these countries were quite fluid and dynamic--an interpretation that departs markedly from the prevalent view of China fixed at the center of a widespread "tribute system." To cope with external affairs in a tumultuous world, Tang China employed a dual management system that allowed both central and local officials to conduct foreign affairs. The court authorized Tang local administrators to receive foreign visitors, forward their diplomatic letters to the capital, and manage contact with outsiders whose territories bordered on China. Not limited to handling routine matters, local officials used their knowledge of border situations to influence the court's foreign policy. Some even took the liberty of acting without the court's authorization when an emergency occurred, thus adding another layer to multipolarity in the region's geopolitics. The book also sheds new light on the ideological foundation of Tang China's foreign policy. Appropriateness, efficacy, expedience, and mutual self-interest guided the court's actions abroad. Although officials often used "virtue" and "righteousness" in policy discussions and announcements, these terms were not abstract universal principles but justifications for the pursuit of self-interest by those involved. Detailed philological studies reveal that in the realm of international politics, "virtue" and "righteousness" were in fact viewed as pragmatic and utilitarian in nature."--Publisher's description